MAGMATISME, SUMBERDAYA MINERAL DAN ENERGI DI TAPANULI SELATAN-SUMATERA UTARA - Isnu Hajar Sulistyawan; Bhakti Hamonangan Harahap (Jurnal Geologi dan Sumberdaya Mineral, 2013)
The result of geological survey in Tapanuli Selatan indicates that there are a relationship between magmatism process and the possibility of mineral and energy occurences. Field observation and supported with laboratory analysis showing some mineral occurs in the area i.e. gold, base metal (Cu, Pb, Zn), zeolit, kaolin, andesitic lava dan tras. Multiple intrusions may control the occurrence of base metals and gold resources and the eruption of some volcanoes was producing another mineral resources. Resources of geothermal also found in Sipirok as another implication of volcanic process in Tapanuli Selatan area. It may related to the activity of Mount Sibualbuali in the past. Occurs as the effect of heat release from the magmatism process, hydrocarbon of Barumun Basin and some layers of coal has found in this area. High calori of coal was occurs in a thin layer of Sihapas Formation.Keywords : magmatism, resources, minerals, hydrocarbon, geothermal